Propofol orchestrates long non-coding RNAs in MCF7 cells, unraveling new avenues for breast cancer intervention - Cigir Biray Avci; Tuba Gokdogan Edgunlu; Tugba Suzek; Neslihan Pinar Ozates; Bakiye Goker Bagca; Aysegul Demirtas Bilgic; Cilem Ozdemir; Bakiye Ugur (Elsevier, 2024)
Long non-coding RNAs (lncRNAs) play a dynamic role in gene expression regulation and serve as potential therapeutic targets in breast cancer. The anticancer effect of propofol, an anesthetic agent, has been proven, but its interaction with lncRNAs has not been adequately investigated. This study aims to reveal the interactions between propofol and lncRNAs and contribute to the understanding of its therapeutic potential in the treatment of breast cancer. We evaluated the effects of propofol on cell viability, apoptosis, and mitochondrial membrane potential in MCF7 cells. The study used qRT-PCR to analyze cancer-related lncRNA expressions following propofol treatment; this was supported by RNA-RNA interaction predictions and in silico functional analysis using selected datasets and the R cluster Profiler GSEABase package. Propofol showed a cytotoxic effect at higher doses in MCF7 breast cancer cells, inducing necrosis. Propofol regulated (IGF2-AS, MRPL23-AS1, PANDAR, HULC) and down-regulated (IWT1-AS, HOXA-AS2, H19, GACAT1, MIAT) the expression levels of various lncRNAs in MCF7 cells. Our research revealed complex interactions of MALAT1 lncRNA with both upregulated and downregulated genes. Additionally, three rRNA genes (LSU-rRNA, RNA45SN3, and SSU-rRNA) were identified to interact with both groups of lncRNAs. Propofol potentially targets chemotherapy resistance by regulating UCA1, LINC-RoR1, and MEG3. Wikipathways' pathway enrichment analysis identified two downregulated lncRNAs, UCA1 and LINC-RoR1, and an upregulated MEG3, implicated in lncRNA-mediated chemotherapeutic resistance mechanisms. Our study illuminates the intricate interplay of lncRNAs and their potential contribution to propofol's anti-cancer effects in breast cancer, offering new avenues for therapeutic exploration and advancement.